The Impact of Perceived Value, Trust and the Mediating Role of Purchase Intention on ChatGPT Purchase Decisions - Abimanyu Siddiq; Lusia Tri Hutami; Putri Dwi Anjani (Eduvest - Journal of Universal Studies, 2026)
This study investigated how perceived value and trust influence purchase intention and purchase decision for paid ChatGPT subscriptions. A quantitative survey was conducted among users who have used ChatGPT and subscribed to GPT Go, Plus, or Pro, using non-probability purposive sampling. The data were analysed with multiple linear regression and a mediation test. The findings show that perceived value and trust both have positive effects on purchase intention. Perceived value and purchase intention also have positive effects on purchase decision, whereas the direct effect of trust on purchase decision is not significant. Furthermore, purchase intention mediates the relationships between perceived value and purchase decision and between trust and purchase decision. These results indicate that users’ evaluations of value and trust toward ChatGPT primarily operate by strengthening their intention to subscribe, which then translates into actual subscription behaviour. The study extends value-based adoption and trust perspectives by connecting them to actual subscription decisions for a generative AI service and offers practical guidance for AI service providers on how to design and communicate value propositions and trust-building mechanisms that effectively convert intention into subscription.